Variance partitioning of deconstructed periphyton communities: does the use of biological traits matter? - Algarte, Vanessa M.; Rodrigues, Liliana; Landeiro, Victor L.; Siqueira, Tadeu [UNESP]; Bini, Luis Mauricio (Springer, 2014)
The use of species traits offers a promising approach to the understanding of the main processes underlying metacommunity patterns. We analyzed samples of periphytic algae in 30 environments of the Upper Parana River floodplain in southeastern Brazil, to test the hypotheses that variation in species composition of algal groups with low dispersal abilities would be mainly explained by spatial variables; on the other hand, algal groups with higher dispersal abilities would be better explained by environmental variables. The variation in community structure was mainly correlated with environmental variables. This result is in line with a growing body of evidence indicating a predominant role of species-sorting processes. The more-refined prediction that the spatial variables would gradually become more important across a gradient of adherence or size was, however, not supported by our analyses. Also, the large unexplained variation suggested that these periphytic communities were assembled by idiosyncratic events, or that other variables that are often neglected in studies of aquatic metacommunities needed to be included.
Keywords: Metacommunity; Periphyton; pRDA; Environmental variables; Aquatic communities; Floodplain